Developing and authenticating an electronic health record–based report card for assessing residents' clinical performance. Issue 2 (30th March 2023) - Sebok‐Syer, Stefanie S.; Dukelow, Adam M.; Sedran, Robert; Shepherd, Lisa; McConnell, Allison; Shaw, Jennifer M.; Lingard, Lorelei
Abstract: Purpose: The electronic health record (EHR) is frequently identified as a source of assessment data regarding residents' clinical performance. To better understand how to harness EHR data for education purposes, the authors developed and authenticated a prototype resident report card. This report card used EHR data exclusively and was authenticated with various stakeholders to understand individuals' reactions to and interpretations of EHR data when presented in this way. Methods: Using principles derived from participatory action research and participatory evaluation, this study brought together residents, faculty, a program director, and medical education researchers ( n  = 19) to develop and authenticate a prototype report card for residents. From February to September 2019, participants were invited to take part in a semistructured interview that explored their reactions to the prototype and provided insights about how they interpreted the EHR data. Results: Our results highlighted three themes: data representation, data value, and data literacy. Participants varied in terms of the best way to present the various EHR metrics and felt pertinent contextual information should be included. All participants agreed that the EHR data presented were valuable, but most had concerns about using it for assessment. Finally, participants had difficulties interpreting the data, suggesting that these data could be presented more intuitively and that residents and faculty may require additional training to fully appreciate these EHR data. Conclusions: This work demonstrated how EHR data could be used to assess residents' clinical performance, but it also identified areas that warrant further consideration, especially pertaining to data representation and subsequent interpretation. Providing residents and faculty with EHR data in a resident report card was viewed as most valuable when used to guide feedback and coaching conversations.